Lysosomal localisation of parallel tubular arrays in chronic lymphocytic leukaemia of T cell origin: an ultrastructural cytochemical study. Issue 2 (February 1982) - Capron, F; PErrot, J Y; Boucheix, C; Reynes, M; Tricottet, V; Bernadou, A; Diebold, J
Abstract : An ultrastructural cytochemical study of lysosomal acid phosphatase was performed on leukemic cells in a case of chronic lymphocytic leukaemia of T cell origin (T-CLL). The cells showed inclusion bodies known as parallel tubular arrays, which often lay within acid phosphatase-positive, membrane-bound spaces. This suggests their lysosomal location.